Certified cause of death in children and young adults with cerebral palsy. Issue 3 (March 1991) - Evans, P M; Alberman, E
Abstract : The status of 732 children suffering from cerebral palsy from the South East Thames region (births from 1970-9) was ascertained at the end of 1989, and copies of death certificates of the 73 children who have died, aged 4 weeks to nearly 16 years, were obtained. Infantile cerebral palsy (ICD Code 343-) was coded as the underlying cause of death in only 16 (22%) cases. On 28 (38%) certificates there was no mention of any form of cerebral palsy, the proportion in which it was not mentioned increasing with age. In 20 (28%) cases the coded underlying cause of death was respiratory, hence in published national statistics the number of deaths from respiratory causes is inflated. A postmortem examination was known to have been performed in 23 cases, but the recorded information was in some cases limited to a 'terminal event'. The importance of good data on the death certificate, and the significance of published national statistics, need to be communicated to all those involved in the certification process if cerebral palsy and other chronic conditions, which raise the relative risk of death, are not to be under-represented.